Efficient Preparation of Imidazo[1,5-a]pyridine-1-carboxylic Acids - Tverdiy, Dmytro O.; Chekanov, Maksym O.; Savitskiy, Pavlo V.; Syniugin, Anatolii R.; Yarmoliuk, Sergiy M.; Fokin, Andrey A. (Synthesis, 2016)
We report a novel and efficient approach to the synthesis of imidazo[1,5-a]pyridine-1-carboxylic acids. By using the reaction of 2-(aminomethyl)pyridine with acyl chlorides followed by one-pot treatment with trifluoroacetic anhydride, 2,2,2-trifluoro-1-imidazo[1,5-a]pyridin-1-ylethanones were obtained, which were then converted into imidazo[1,5-a]pyridine-1-carboxylic acids in high preparative yields through haloform cleavage.
Keywords: amides; cyclization; heterocycles; bicyclic compounds; acylation